Kukkuta (Chicken) in Ayurveda Literature - Manju Prasad. M.K,; Anand Katti, (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda Samithas directly or indirectly touch upon each dimension of human life. The leads of every science connected to health can be traced in Ayurveda. Ahara Dravyas explained by Acharays plays an important role in prevention and curation of diseases. Meat of various animals and birds are mentioned with their nutritive and therapeutic values under the sub class of Mamsa varga. Kukkuta is one such bird belonging under Vikshira varga. Among many birds, the instances of Kukkuta (Chicken) outplay the importance of others birds. Chickens are the important source of meat and egg which greatly benefits human population with its high nutritive profile. Kukkuta and its eggs are not only used for its food values but also recommended for therapeutic values in various diseases, formulations and in as Pathya-apathya in Ayurveda. As the information on Kukkuta is scattered, the present article compiles, analyses and discuss the utility of Kukkuta in detail